Appraisal of Ground Water Quality and its Impact on Irrigated Soils in Khartoum State, Sudan (University of Khartoum Journal of Agricultural Sciences, 2025)
A study was undertaken to appraise the quality and impact ofwell waters on irrigated soils of fifty farms widely spread in KhartoumState, Sudan. Water quality indicators and pertinent soil properties weremeasured by standard procedures. The determinations were electricalconductivity of water (ECw) and soil saturation extracts (ECe) andsoluble Na+ , K+ , Ca++ + Mg++ , Cl -, HCO3- and SO4--. Sodium adsorptionratio (SAR), residual sodium carbonate (RSC), theoretical pH (pHc) andLangeleir's saturation index (LSI) were computed. A questionnaireincluding pertinent well and farm data and information was filled. ECwranged between 0.4 to 4.8 dS/m. According to the United States SalinityLaboratory (USSL) classification system, 30% of the water samples liedwithin the medium salinity class, 62% lied within the high salinity classand 8% within the very high salinity class. In agreement with USSL,highly significant linear correlations between ECw and total saltconcentration of water expressed in mmole+ /l or mg/l with 99%accountability were found. Ninety-eight percent of the water sampleswere non-sodic. Only one water sample gave a SAR value equal to 19.1and the remaining waters had SAR ranging between 1.1 and 9.4. RSC wasnegative for all water samples with the exception of two samples (4%)that gave RSC values ≤ 0.6 and thus within the safe level. In general, LSIdata agreed with RSC data. The well waters were predominantly Ca-Na/SO4 =Cl waters. The results showed that 70% of the top layer of the